Continuous Cooling Compressor for water refrigerant heat pump. Issue 1 (September 2021) - Shoyama, T.; Sun, H.; Kawano, B.; Matsui, M.
Abstract: A turbo compressor was developed for water refrigerant heat pumps equipped with continuous cooling compression, in which the vapour is continuously cooled during the compression process by the latent heat of evaporation of the liquid water refrigerant sprayed into the impeller channels. One of the disadvantages of water refrigerant is that the discharge temperature during vapour compression is higher than that of fluorocarbon refrigerant. Multi-stage compression with intercooling are one of the solutions, the system becomes large. In continuous cooling compression, fine particles of water are sprayed from a nozzle embedded inside the impeller, and the water vapour in compression process is directly cooled to the saturation temperature. Therefore, if sufficient amount of spray is present, the compression process follows the saturation line in p-h diagram. Water is supplied to the spray nozzle after pressurized to 10 MPa or more using the centrifugal effect of rotor rotation. A small nozzle was developed that suppresses rotor imbalance and can withstand the load of centrifugal force. A followability index was defined as a reference for the droplets to follow the vapour flow and evaporate before colliding with the blade surface. A water-refrigerant heat pump system was constructed, and the degree of superheat of the discharged vapour was evaluated while changing the spray amount. Increasing the amount of spray decreased the superheat but COP also decreased. Saturated compression was demonstrated above a certain amount of spray, but the impeller flow was choked due to the droplet evaporation. It is desirable to assume a sufficient choke margin, or to develop a special CFD code that can take into account the droplet evaporation.